Membudayakan Protokol Kesehatan Di Lingkungan Perumahan Demi Pengendalian Penyebaran Covid-19 - Susilowati, Indah; Nurkhalim, Ratna Frenty; Jayanti, Krisnita Dwi (Universitas Nusantara PGRI Kediri, 2021)
In the new normal era people are allowed to do their daily activities even though there are still restrictions. However, the lack of awareness in implementing health protocols is significant with an increase in the number of people confirmed positive for Covid 19. Himbauan in anticipating the spread and suppressing the number of Covid 19 infections is increasingly carried out. The purpose of this community service is to increase public awareness in implementing health protocols that are useful in breaking the chain of spread of Covid-19 during the pandemic. The method is observation in the community in one of the residential environments in complying with health protocols, then counseling to the community, and monitoring and evaluation of compliance implementing health protocols. The results of the activities carried out showed that the public knows about Covid 19 infection, how to transmit and prevent it, how to wear the appropriate mask, is able to apply physical distancing in daily life, and knows about how to ethics cough well and correctly. Public knowledge is also evaluated on the compliance of implementing the procedural health protocols that have been described. Awareness and willingness to implement health protocols is one of the keys to self-protection from infections that are harmful to health.